(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
The article discusses the process of developing critical thinking skills in students during their independent learning. The relevance of the research is determined by the need to develop analytical, reflective, and evaluative abilities in students for successful professional activity in the context of the modern information society. The article highlights the theoretical aspects of critical thinking, its role in the educational process, and the effectiveness of applying various methods and techniques in the process of students’ independent work. Particular attention is given to the use of problem-oriented tasks, discussions, case methods, and other forms of active learning that contribute to the development of independence and a critical approach to solving academic and professional tasks. It is expected that the implementation of such approaches will significantly improve the quality of the educational process, help prepare students who are able to independently analyze information, make well-founded decisions, and argue their point of view.